2010
DOI: 10.1016/j.jpaa.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi groups are conjugacy separable

Abstract: a b s t r a c tWe prove that non-uniform arithmetic lattices of SL 2 (C) and consequently the Bianchi groups are conjugacy separable. The proof is based on recent deep results of Agol, Long, Reid and Minasyan. The conjugacy separability of groups commensurable with limit groups is also established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…For this reason, one defines a group to be hereditarily conjugacy separable if every finite-index subgroup is conjugacy separable. We will now show that, in the 3-manifold context, one can apply a criterion of Chagas-Zalesskii [ChZ10] to prove that hereditary conjugacy separability passes to finite extensions.…”
Section: Proofsmentioning
confidence: 99%

3-manifold groups

Aschenbrenner,
Friedl,
Wilton
2012
Preprint
“…For this reason, one defines a group to be hereditarily conjugacy separable if every finite-index subgroup is conjugacy separable. We will now show that, in the 3-manifold context, one can apply a criterion of Chagas-Zalesskii [ChZ10] to prove that hereditary conjugacy separability passes to finite extensions.…”
Section: Proofsmentioning
confidence: 99%

3-manifold groups

Aschenbrenner,
Friedl,
Wilton
2012
Preprint
“…The crucial concept is the notion of a special group, introduced by Haglund and Wise [13]. † Minasyan proved that special groups are conjugacy separable [24], while Chagas and the third author gave conditions under which conjugacy separability passes to finite extensions [10]. Taking these two results together, it follows that, if N is a hyperbolic 3-manifold and π 1 (N ) is virtually special (that is, π 1 (N ) has a special subgroup of finite index), then π 1 (N ) is conjugacy separable.…”
Section: Conjugacy Separabilitymentioning
confidence: 99%
“…Many hyperbolic 3-manifold and orbifold groups are known to be virtually special [7,8,10,11], among them non-cocompact arithmetic and standard cocompact arithmetic lattices. Wise has announced a proof that the fundamental group of any hyperbolic 3-manifold containing an embedded geometrically finite surface is virtually special [31]; the heart of his proof is contained in [32].…”
Section: Conjugacy Separabilitymentioning
confidence: 99%
“…In [25] the first author showed that right angled Artin groups are hereditarily conjugacy separable. This result was subsequently used to prove conjugacy separability of Bianchi groups [7], 1-relator groups with torsion [26] and fundamental groups of compact 3-manifolds [17]. In fact, in [25] it was shown that any virtually compact special group G contains a conjugacy separable subgroup of finite index.…”
Section: Introductionmentioning
confidence: 97%